The uneducated and the politics of knowing in 'post truth' times: Ranciere, populism and in/equality. Issue 2 (4th March 2021) - Gerrard, Jessica
ABSTRACT: Contemporary politics has brought the figure of the 'uneducated' into glaring view, from Trump's 'love' of the 'poorly educated' to analyses suggesting a supposed 'uneducated populous' is responsible for the rise of far-right politics. In this paper I respond to this so-called 'post-truth' contemporary moment by considering how education underpins many 'progressive' or 'left' responses to rightist political impulses and flesh out the repercussions of such a stance. Specifically, I explore the ramifications for the notion of the 'educated' through a critical reading of political philosopher Jacques Ranciere. I suggest the need to understand the question of education (and 'poor education') within the context of capitalist political interests and the linking of educational institutions with elitism and power.